Multifunctional supramolecular self-assembly system for colorimetric detection of Hg2+, Fe3+, Cu2+ and continuous sensing of volatile acids and organic amine gases. Issue 22 (29th May 2019) - Cao, Xinhua; Li, Yiran; Yu, Yicheng; Fu, Shiying; Gao, Aiping; Chang, Xueping
Abstract : A multifunctional supramolecular self-assembly system was prepared for colorimetric detection of Hg 2+, Fe 3+, Cu 2+ and continuous sensing of volatile acids and organic amine gases through three different modes. Abstract : A novel multifunctional gelator (1 ) based on an azobenzene derivative was designed and characterized. This compound could gelate some solvents including hexane, petroleum ether, DMSO, acetonitrile and ethanol through a heating–cooling procedure. The self-assembly process in different solvents was studied by means of UV-vis absorption and Fourier transform infrared (FTIR) spectra, field emission scanning electron microscopy (FESEM), rheological measurements, X-ray powder diffraction and water contact angle experiments. Interestingly, compound1 had a high-contrast colorimetric detection ability towards Hg 2+, Cu 2+, Fe 3+ and volatile acids and further organic amine gases in solution through its color change. At the same time, organogel1 in acetonitrile also exhibited detection performance through a color or gel state change. In the response process, the self-assembly structures were changed from a nanofiber into a microsphere under induction by analytes. More significantly, film1 could continuously detect volatile acids and organic amine gases. The number of cycles of film1 for the detection of volatile acids and organic amine gases was at least seven times. The limit of detection (LOD) of film1 towards TFA was calculated to be 0.0848 ppb. The sensing mechanisms were studied using 1 HNMR, FESEM, UV-vis absorption spectra and HRMS. The intramolecular cyclization occurred on molecule1 and a H2 S molecule was lost during the detection process of Hg 2+ . It was proposed that the –NN– bonding could be coordinated by Fe 3+ and Cu 2+ and this further induced the absorption spectra and color change. For a volatile acid, it was possible that the volatile acid was combined with the N, N -dimethyl amine group of molecule1 . This research opens up a novel pathway to the fabrication of supramolecular self-assembly gels to detect polymetallic ions and trace volatile acids in the environment.